2002
DOI: 10.1093/jhered/93.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Amplification of Microsatellite Markers From Colubroid Snakes in European Natricines (Serpentes: Natricinae)

Abstract: Eighteen microsatellite loci developed for a range of snake species (New World natricines, elapids, crotalids) were tested against European natricines (Natrix natrix, N. maura, and N. tessellata) in cross-species amplification experiments. Five loci were polymorphic (average expected heterozygosity 0.749 for a population of N. natrix in Amsterdam, mean sample size 47.8) and three loci were monomorphic. The remainder could not be consistently scored or failed to amplify. Further tests on single individuals of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…One important event in differentiation of snakes was the nonsynonymous mutations in the homeobox gene HOXA-13 that may be responsible for the absence of legs [Kohlsdorf et al, 2008]. One important genetic marker are microsatellites, which are not directly involved in the evolution of snakes, however useful for understanding the genetic processes [Hille et al, 2002;Lukoschek et al, 2008]. We cannot forget to add the Horizontal Gene Transfer to these genetic mechanisms.…”
mentioning
confidence: 99%
“…One important event in differentiation of snakes was the nonsynonymous mutations in the homeobox gene HOXA-13 that may be responsible for the absence of legs [Kohlsdorf et al, 2008]. One important genetic marker are microsatellites, which are not directly involved in the evolution of snakes, however useful for understanding the genetic processes [Hille et al, 2002;Lukoschek et al, 2008]. We cannot forget to add the Horizontal Gene Transfer to these genetic mechanisms.…”
mentioning
confidence: 99%
“…Hille et al, (2002) reported that monomorphic loci observed in cross amplification could be due to null heterozygous condition. Four (GSSR-43, GSSR-96, GSSR-113 and BSSR-8) out of thirty nine SSR markers revealed polymorphic loci.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five microsatellite loci, derived from four species of snakes, were evaluated for the parentage test [Hb48, Hb65, and Hb70: Hoplocephalus bungaroides [Burns and Houlden, 1999]; Eobm1-4, Eobm10, Eobm13, Eobm16, Eobm34, Eobm358, Eobm366, and Eobm373: Elaphe obsoleta [Blouin-Demers and Gibbs, 2003]; Nsm2-4, Nsm6-8 and Nsm9b: Nerodia sipedon sipedon [Prosser et al, 1999;Hille et al, 2002]; Ts1-4: Thamnophis sirtalis [McCracken et al, 1999;Hille et al, 2002] (IDT Coralville, IA)]. Despite the use of 25 microsatellites, less than half (Eobm1, Eobm3, Eobm10, Eobm13, Eobm16, Eobm34, Eobm366, and Eobm373) were used for paternity exclusion analysis [Groot et al, 2003;King and Withler, 2005].…”
Section: Genetic Analysismentioning
confidence: 99%